Inhibition potency of drumstick leaf extract (Moringa oleifera) towards Aeromonas hydrophila: Preliminary Study for Aeromoniasis Treatment. - Hapsari Kenconojati; Nina Rofi' Rukman (Airlangga University, 2019)
The aim of this study was to know antibacterial potency of ethanolic extract of drumstick leaf against Aeromonas hydrophila in vitro. Total flavonoid, alkaloid, tannin and saponin of the ethanolic drumstick leaf extract were analyzed using spectrophotometry. Antibacterial activity test was carried out by disk diffusion and tube dilution method. Ethanolic extract of drumstick leaf contained flavonoids total as 71.9 mg quercetine equivalent/g, alkaloids total as 3 mg quinine equivalent/g, tannin as 24.7 mg tannic acid equivalent/g and saponin as 44.4 mg/g. The result of antibacterial test showed significant inhibition of Aeromonas hydrophila by drumstick leaf extract (P<0.05). The highest inhibition zone was produced by drumstick leaf extract with concentration of 100% which is 9.9± 0,162 mm. The minimum inhibition concentration (MIC) of drumstick leaf extract is 3.125%, while the minimum bactericidal concentration (MBC) is 6.25%. Based on this study, it can be concluded that drumstick leaf can be used as an alternative natural product of antibacterial agent which can be applied especially in aquaculture.